2013
DOI: 10.1002/hep.26081
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 and palmitic acid cooperatively contribute to the development of nonalcoholic steatohepatitis through inflammasome activation in mice

Abstract: Innate immune signaling associated with Toll like receptors (TLRs) is a key pathway involved in the progression of nonalcoholic steatohepatitis (NASH). Here we show that both TLR2 and palmitic acid are required for activation of the inflammasome, IL-1α and IL-1β, resulting in the progression of NASH. Wild type (WT) and TLR2−/− mice were fed a choline deficient amino acid defined (CDAA) diet for 22 weeks to induce NASH. Bone marrow transplanted-TLR2 chimeric mice were generated after the recipient mice were let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(198 citation statements)
references
References 47 publications
7
189
0
2
Order By: Relevance
“…At the same time, TLR2 activation can be triggered by hepatic lipid accumulation (Miura et al 2013). Upon activation, TLR2, TLR4, and TLR9 signal through the MyD88 pathway, activate NF-kb, and result in the production of proinflammatory cytokines and chronic inflammation (Miura et al 2013, Roh & Seki 2013.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, TLR2 activation can be triggered by hepatic lipid accumulation (Miura et al 2013). Upon activation, TLR2, TLR4, and TLR9 signal through the MyD88 pathway, activate NF-kb, and result in the production of proinflammatory cytokines and chronic inflammation (Miura et al 2013, Roh & Seki 2013.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we reconstituted hematopoietic cells by generating chimeric mice, in which BM cells lacking TLR were transplanted after the administration of lethal irradiation combined with the depletion of resident macrophages (9,24). Transplanting Tlr4 Ϫ/Ϫ BM cells resulted in the suppression of inflammatory cell infiltration in the Pten ⌬hep mice compared with that observed in the control BM or Tlr2 Ϫ/Ϫ BM cells (Fig.…”
Section: Tlr4 On Hematopoietic Cells Contributes To Tumor Growthmentioning
confidence: 99%
“…⌬hep Mice-Of the various hematopoietic cells expressing TLR4, we focused on macrophages because these cells are a major source of proinflammatory cytokines, which promote the progression of steatohepatitis (21,24). Ly6C is a marker for inflammatory macrophages derived from the BM (25).…”
Section: Hepatic Macrophages Contribute To the Tumor Growth In The Ptenmentioning
confidence: 99%
“…Lipid-derived products (e.g., free fatty acids and cholesterol) themselves are endogenous DAMPs, and directly activate the inflammasome via both TLR and NLR pathways (13,14). A recent study also demonstrates that ER stress also enhances inflammasome activity through CHOP (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in nonalcoholic fatty liver disease (NAFLD), saturated fatty acids (SFA) but not poly-unsaturated fatty acids (PUFA) have been shown to cause inflammation and cell death (13,14). However, it has also been shown that PUFAs can exacerbate liver injury and markers of inflammation in a murine NAFLD model (15).…”
Section: Introductionmentioning
confidence: 99%